Delivering knock your socks off service (AMACOM, 2007)
Written in the same accessible and humorous style that made this book a classic, this title features brand-new chapters on important topics such as understanding cultural and generational differences in customers, plus fresh anecdotes and never-before-seen illustrations by cartoonist John Bush.